Design, Development And Validation Of An Enhanced Instructional Design Model For Blended Learning - Ong, Wei Siang (2024)
Blended learning integrates online learning mode with face-to-face (FTF) learning mode as a whole learning system by providing students more flexibility to customize their learning experience. In Malaysia, many studies related to blended learning were conducted in tertiary education compared to the secondary education. However, none of the research focus on the design and development of an ID model for blended learning. In addition, the Ministry of Education Malaysia has recommended school teachers to employ blended learning as one of the 21st century pedagogical approaches in teaching and learning. A structured and systematic approach based on instructional and theoretical foundations is required for school teachers to design and develop a blended learning lesson. Therefore, this study utilizes Design and Development Research (DDR) approach, in which an initial instructional design (ID) model for blended learning was designed and developed based on theoretical foundations. This is known as model development, one of the projects emphases in the model research. Then, an exploratory multi-sequential mixed method design was employed to validate the initial ID model by subject matter experts, school teachers and students. This is known as model validation, another project emphasis in the model research. Three types of internal validations were used in sequence to validate the ID model by the subject matter experts and school teachers via Delphi technique, in-depth interview, and teacher survey.